The Effect of Performance Allowances and Organizational Justice on Employee Performance through Organizational Commitment Bekasi Religious Court Office - Aditya Rahmat Setiawan; Partogi S Samosir; Eddy Sanusi Silitonga (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The purpose of this study is to determine the effect of performance allowances and organizational justice on employee performance through organizational commitment at the Bekasi Religious Court. This study uses quantitative research with a descriptive approach. The population in this study were all employees at the Bekasi Religious Court, namely 60 employees. The sampling technique used in this study was saturated sampling which is included in non-probability sampling. Non-probability sampling is a sampling technique that does not provide equal opportunities or chances for each member of the population to be selected as a sample. The results of the study indicate that the performance allowance received makes employees perceive the performance allowance as a form of appreciation for work contributions, thus encouraging the formation of a stronger organizational commitment; the perception of justice tends to be seen as a normative system obligation, so that its existence does not directly increase the psychological attachment of employees to the organization.